Influence of 2,4,6-trinitrotoluene on hemolymph of Procambarus virginalis (Decapoda, Cambaridae) - O. M. Marenkov; I. V. Holub; O. S. Nesterenko; I. I. Borovyk; V. O. Kurchenko (Regulatory Mechanisms in Biosystems, 2026)
2,4,6- t rinitrotoluene (TNT) is a xenobiotic that exerts toxic effects on all forms of life. Due to active military operations, unco n trolled amounts of this compound are released into ecosystems, making it essential to investigate the potential adaptive responses of tissues and organs. The reaction of hemolymph cells of marble crayfish Procambarus virginalis (Lyko, 2017) to the effects of 2,4,6-trinitrotoluene (TNT) was studied in a chronic model experiment. The relevance of the topic is due to the toxic load of expl o sives on aquatic ecosystems of Ukraine as a result of military operations. Exposure to TNT at concentrations of 25 and 50 mg/L caused significant morphological changes in the immune system cells of the crustaceans. When exposed to 25 mg/L of TNT for 4 weeks, an increase in the average area of hyalinocytes by 79% was observed (from 145.3 μm² in the control to 260.1 μm²), which may indicate the activation of the functional state of hemocytes and the mobilization of the immune response. Such an adaptive reaction indicates a possible increase in the phagocytic or secretory activity of cells in response to a sublethal concentration of the toxicant. It was found that under the influence of a lower concentration, the area of hyalinocytes was 1.79 times larger than in the control, which indicates an active immune response. However, under the influence of a higher concentration, the area of the same cells decreased by 1.25 times, and the area of blasts – by 1.44 times compared to the control, which may indicate an intensive inh i bition of hematopoiesis. Blasts were especially sensitive to a high concentration of TNT – their area decreased by 30.6% (from 85.8 to 59.6 μm²). This indicates the inhibition of the maturation processes of young cells or the death of cell precursors under conditions of chronic toxic stress. The application of morphometric analysis of hemolymph cells as a sensitive biomarker allows to assess both adaptive and destructive changes in invertebrates under the influence of xenobiotics. The obtained data can be used for biomonito r ing the condition of water bodies contaminated with warfare-related substances.